2018
DOI: 10.3382/ps/pey141
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communication between Lactobacillus spp. isolated from poultry in the inhibition of Salmonella Heidelberg—proof of concept

Abstract: Bacterial communication has become an increasingly studied topic aiming at the discovery of new products to aid the treatment of diseases for which conventional options do not work. The production of safe foods, free of pathogens, has been receiving increasing attention due to market demands for food products of high quality and free of residues. This study assessed the communication between Lactobacillus spp. during the in vitro inhibition of Salmonella Heidelberg (SH) and the impact an autoinducer produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…It has been repeatedly confirmed that lactobacilli produce metabolites that suppress the growth of Salmonella [28][29][30]. Lactobacilli also produce metabolites affecting host gene expression [31,32].…”
Section: Discussionmentioning
confidence: 94%
“…It has been repeatedly confirmed that lactobacilli produce metabolites that suppress the growth of Salmonella [28][29][30]. Lactobacilli also produce metabolites affecting host gene expression [31,32].…”
Section: Discussionmentioning
confidence: 94%
“…While potentially less practical, probiotics can also be delivered to chicks orally shortly after hatch. A number of studies found that single oral doses of probiotics on day 0 or 1 of life can protect against Salmonella early in life, leading to reductions in Salmonella prevalence in the spleen and liver (Yang et al., 2014) and ceca (Higgins et al., 2010; Marietto‐Goncalves et al., 2014; Schneitz et al., 2016; Sornplang et al., 2015; Telg & Caldwell, 2009; Waewdee et al., 2012), and reducing cecal counts by 0.9–3 log 10 CFU/g (Menconi et al., 2011; Nakphaichit et al., 2019; Okamoto et al., 2018; Prado‐Rebolledo et al., 2017; Revolledo et al., 2009; Telg & Caldwell, 2009). Treatments consisting of multiple oral doses of a Lactobacillus probiotic starting from day 1 of life were also found to reduce cecal Salmonella (Chen et al., 2012; Olnood et al., 2015).…”
Section: Primary Productionmentioning
confidence: 99%
“…A number of studies found that single oral doses of probiotics on days 0 or 1 of life can protect against Salmonella early in life, where they led to reductions in Salmonella prevalence in the spleen and liver [38] and ceca [39][40][41][42][43], and reduced cecal counts by 0.9-3 log10 CFU/g [43][44][45][46][47]. Treatments consisting of multiple oral doses of a Lactobacillus probiotic starting from day 1 of life were found to reduce cecal Salmonella [48,49].…”
Section: Hatcherymentioning
confidence: 99%